Deficits in fronto-posterior interactions point to inefficient resource allocation in schizophrenia - Sharma, Anuradha; Weisbrod, Matthias; Kaiser, Stefan; Markela-Lerenc, Jaana; Bender, Stephan (Acta psychiatrica Scandinavica, 2011)
Sharma A, Weisbrod M, Kaiser S, Markela-Lerenc J, Bender S. Deficits in fronto-posterior interactions point to inefficient resource allocation in schizophrenia. Objective: Fronto-posterior networks have been implicated in various cognitive processes that are impaired in schizophrenia. This is the first study on time and frequency resolved fronto-posterior coherence during cognitive control in schizophrenia. Method: We examined 16 schizophrenic/schizoaffective patients and 20 age-matched controls performing a choice-reaction task. Fronto-posterior coherence was analyzed for event-related increases with respect to the inter-trial interval. Furthermore, we compared the two groups for event-related coherence during the task-related time intervals which showed a significant coherence increase with respect to the inter-trial interval, as well as for absolute coherence during the inter-trial interval. Results: Event-related coherence was significantly reduced in patients during time intervals (0-250 ms poststimulus) when controls showed significant event-related coherence increases. However, patients showed significantly higher absolute coherence during the inter-trial interval. These results pointed to differential deficits in fronto-posterior connectivity during the inter-trial interval and task-related conditions in schizophrenia. Conclusion: Cognitive deficits in schizophrenia might be driven by abnormal fronto-posterior communication. Task-related hypo-connectivity and inter-trial interval hyper-connectivity point to resource allocation deficits. The timing of cortico-cortical interactions during crucial task-related intervals may be impaired, while frontal and posterior areas may exhibit increased interactions between the trials.
First published: 16 September 2010
Gesehen am 30.11.2022